Os conhecimentos basilares da docência e o pensamento reflexivo no estágio curricular supervisionado de Química - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
In this qualitative research, we propose to analyze how the teaching knowledge is mobilized in different time-places of Supervised Curriculum Internship I and II and how the reflection influences this process. The research was developed with a group of Chemistry education program of the Ponta Grossa State University (UEPG) during Supervised Curricular Internship I and II. Our data are based on the materials produced during the internship disciplines developed in the period of 2017 and 2018. To analyze the data we adopted the categories of the Knowledge Model of Science Teachers proposed by Abell (2007) and the Zeichner Reflexive Teaching Indicator Liston (1985). The Discursive Textual Analysis methodology was used with support of the ATLAS.ti 8.0 software in the data set analysis. The results point to the predominance of the mobilization of the Pedagogical Knowledge of Content, based on the instructional strategies for teaching in a certain content and the promotion of reflection based on the self-assessment in relation to the actions developed during all the activities of the internship. Thus the research highlights the importance of the variety of activities developed in the Supervised Curricular Internship, which pass through different teaching knowledge.
Keywords: Estágio Curricular Supervisionado; Base de Conhecimentos para a Docência; Reflexão; Supervised Internship; Knowledge Base for Teaching; Reflection; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA